The morphology and the histology of the genital system of Theba pisana (Muller) (Pulmonata: Helicidae) - Noyce, A. G (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1970.